Exercise to Lose Money? Irrational Exercise Behavior from the Chinese Warrants Market. Issue 5 (19th March 2013) - Liao, Li; Li, Zhisheng; Zhang, Weiqiang; Zhu, Ning
Abstract Using a market‐level exercise data set and an individual‐level trading data set between August 2006 and June 2009, this study examines the incidence of two types of irrational exercise behavior in the Chinese warrants market. We find that 121.64 million shares of warrants (0.64% of all warrants) were either exercised with an immediate loss or failed to be exercised, resulting in foregone risk‐free profits. These irrational exercises caused warrant holders to lose over 717.79 million Yuan. Some of the irrational behavior can be attributed to "entertainment seeking" and the "T + 1" rule practiced in the Chinese security market, but the majority is attributed to warrant holders' ignorance and/or negligence of warrant mechanics. Our findings provide additional field evidence of clearly irrational exercise behavior in a derivatives market. We also find that investor education, information and guidance provision can mitigate the incidence of irrational exercise behavior significantly. © 2013 Wiley Periodicals, Inc. Jrl Fut Mark 34:399–419, 2014